2007
DOI: 10.1016/j.mod.2006.09.005
|View full text |Cite
|
Sign up to set email alerts
|

BMP signaling regulates PGC numbers and motility in organ culture

Abstract: Members of the bone morphogenetic protein (BMP) family play diverse roles in multiple developmental processes. However, in the mouse, mutations in many BMPs, BMP receptors and signaling components result in early embryonic lethality making it difficult to analyze the role of these factors during organogenesis or tissue homeostasis in the adult. To bypass this early lethality, we used an organ culture system to study the role of BMPs during primordial germ cell (PGC) migration. PGCs are the embryonic precursors… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
63
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(67 citation statements)
references
References 55 publications
4
63
0
Order By: Relevance
“…Consistent with this, loss of function of the receptor for FGF7, FGFR2-3b results in reduced germ cell numbers (Takeuchi et al, 2005). In addition, BMPs regulate PGC numbers and motility in culture (Dudley et al, 2007;Ross et al, 2007). BMPs are also required for regulation of pluripotency in ES cells (Ying et al, 2003) and for recruitment of PGCs from the proximal epiblast during germ line specification (Lawson et al, 1999;de Sousa Lopes et al, 2004).…”
Section: Survival and Proliferation: Key Aspects Of Early Germ Cell Dmentioning
confidence: 71%
“…Consistent with this, loss of function of the receptor for FGF7, FGFR2-3b results in reduced germ cell numbers (Takeuchi et al, 2005). In addition, BMPs regulate PGC numbers and motility in culture (Dudley et al, 2007;Ross et al, 2007). BMPs are also required for regulation of pluripotency in ES cells (Ying et al, 2003) and for recruitment of PGCs from the proximal epiblast during germ line specification (Lawson et al, 1999;de Sousa Lopes et al, 2004).…”
Section: Survival and Proliferation: Key Aspects Of Early Germ Cell Dmentioning
confidence: 71%
“…The murine testis is formed from genital swellings ventral to the mesonephros, which are populated by migrating primordial germ cells at E10.5 (Wilhelm and Koopman, 2006). BMP signaling regulates primordial germ cell number, proliferation and migration, yet no role had been defined in testicular somatic cells (Hu et al, 2004;Puglisi et al, 2004;Dudley et al, 2007). No germ cell defects were observed in Alk3 IMP null mice, consistent with lack of expression of Rarb2-Cre in these cells.…”
Section: Alk3 Signaling Regulates Mesonephric Derived Testicular Popumentioning
confidence: 97%
“…Id1 is downstream of the BMP/phosphorylated Smad pathway and functions as a dominant-negative binding factor for HLH genes (Norton et al, 1998). However, phosphorylated Smad1, 5 and 8 are not detected in migrating PGCs (Dudley et al, 2007). Thus, Id1 has to be upregulated by another pathway.…”
Section: Research Articlementioning
confidence: 99%
“…S7A in the supplementary material). Although the mechanism of transcriptional regulation of Id1, which bypasses the BMP/phosphorylated Smad pathway (Dudley et al, 2007), is unclear, Id1 might be directly downstream of Nanog in PGCs, as shown by the binding of Nanog to Id1 in ESCs (Kim et al, 2008).…”
Section: Changes In Gene Expression Profile Upon Nanog Knockdown In Ementioning
confidence: 99%